Pengaruh Keikutsertaan ibu hamil dalam kelas ibu hamil terhadap tingkat pengetahuan dan sikap ibu tentang ASI Eksklusif - Pramidya Ujiana; Sari Hastuti; Sabar Santoso (Poltekkes Kemenkes Yogyakarta, 2014)
Exclusive breastfeeding is one program that is quite difficult to develop because it is associated with many social problems in the community. By SDKI infants died per year, or 430 babies per day. According to UNICEF, (2008), optimal breastfeeding in infants under two years of age have the greatest potential impact on child survival of ail preventive measures, the potential to prevent 1.4 million deaths in children under five in developing countries. Coverage rate of exclusive breastfeeding in the province in 2010 was 40.57% and the coverage rate is still half of the expected national targets. Aimto determine the effect of maternal participation in aclass of pregnant women to the level of knowledge and attitude of mothers on exclusive breastfeeding. This study uses cross- sectional study. Subjects were pregnant women in the work area of Puskesmas Kotagede 1 in 2013. Variable in this study is the participation of pregnant women in a class of pregnant women as independent variables and the knowledge and attitude of mothers on exclusive breastfeeding as the dependent variable. Primary data obtained through questionnaires to divide pregnant women.Likelihood analysis using chi square influence to influence participationwith knowledge and Chi square for the effect of participation with an attitude. Results: The results of the effect of participation with knowledge of the results obtained ??2sebesar 0,00 RP 0.93 with 95%Cl (0.59- 1.49) and for participation by the attitude didapakan results ??2 at 0.78, the value of RP pregnant women whohave not pregnant women attended classes ona lowknowledge levelof 0.12with 95%Cl (0.01-1.16)while the value of RP pregnant womenwho have never been pregnant women attend classes on the level of knowledge sufficient for 5.76with 95%Cl (0.81- 40.8).Conclusion: the participation of pregnantwomen in a class of pregnant women did not affect the level of knowledge and participation of pregnant women in a class of pregnan twomen affect maternal attitudes on exclusive breastfeeding